Alloxazine-Based Ligands and Their Ruthenium Complexes as NADH Oxidation Catalysts and G4 Binders - Móran Plata, Maria Jesus (2024)
Flavin-like ligands (L-1 and L-2) with extended πconjugation were synthesized using microwave-assisted techniques. An N,N-chelating fragment was integrated into alloxazine units, providing binding sites for metal ions while retaining redox activity. The complexation capability of L-1 and L-2 with two prototypical Ru-scaffolds was examined to design Ru(II) complexes (M-1 and M-2), whose electronic properties were studied and compared with their corresponding ligands via absorption and emission spectroscopy, computational analysis (density functional theory (DFT) and time-dependent DFT (TD-DFT)), and cyclic voltammetry (CV). The ability of L-1 and M-1 to undergo alloxazine/isoalloxazine tautomerization was demonstrated to play a crucial role in the photocatalytic oxidation of NADH, including under green and red wavelengths. Moreover, the interaction of M-1 and M-2 with B-DNA and G-quadruplex structures was investigated. M-2 showed high stabilization of Kit1 and h-Telo oligonucleotides. Meanwhile, M-1 demonstrated switchable emissive properties with B-DNA and induced conformational changes in the h-Telo G-quadruplex structure.